Construction of Feminism and Gender Equality in Social Media - Ariani, Diah; Sunarto, Sunarto (Budapest International Research and Critics University, 2021)
The criticism that produced BPFA in the Beijing Conference did not necessarily pave the way for gender equality. From the report